Why European and United States drug regulators are not speaking with one voice on anti-influenza drugs: regulatory review methodologies and the importance of ‘deep’ product reviews - Mulinari, Shai (Health Res Policy Syst, 2017)
BACKGROUND: Relenza represents the first neuraminidase inhibitor (NI), a class of drugs that also includes the drug Tamiflu. Although heralded as breakthrough treatments in influenza, NI efficacy has remained highly controversial. A key unsettled question is why the United States Food and Drug Administration (FDA) has approved more cautious efficacy statements in labelling than European regulators for both drugs. METHODS: We conducted a qualitative analysis of United States and European Union regulatory appraisals for Relenza to investigate the reasons for divergent regulatory interpretations, pertaining to Relenza’s capacity to alleviate symptoms and reduce frequency of complications of influenza. RESULTS: In Europe, Relenza was evaluated via the so-called national procedure with Sweden as the reference country. We show that FDA reviewers, unlike their European (i.e. Swedish) counterpart, (1) rejected the manufacturer’s insistence on pooling efficacy data, (2) remained wary of subgroup analyses, and (3) insisted on stringent statistical analyses. These differences meant that the FDA was less likely to depart from prevailing regulatory and scientific standards in interpreting trial results. We argue that the differences are explained largely by divergent institutionalised review methodologies, i.e. the European regulator’s reliance on manufacturer-compiled summaries compared to the FDA’s examination of original data and documentation from trials. CONCLUSIONS: The FDA’s more probing and meticulous evaluative methodology allowed its reviewers to develop ‘deep’ knowledge concerning the clinical and statistical facets of trials, and more informed opinions regarding suitable methods for analysing trial results. These findings challenge the current emphasis on evaluating regulatory performance mainly in terms of speed of review. We propose that persistent uncertainty and knowledge deficits regarding NIs could have been ameliorated had regulators engaged in the public debates over the drugs’ efficacy and explained their contrasting methodologies and judgments. Regulators use major resources to evaluate drugs, but if regulators’ assessments are not effectively disseminated and used, resources are used inefficiently.